Exploring how children and adolescents talk about coping strategies relating to loneliness using reflexive thematic analysis: a qualitative study - Burke, Lauren; Verity, Lily; Riddleston, Laura; Fuhrmann, Delia; Qualter, Pamela; Lau, Jennifer Y. F.; Demkowicz, Ola (Frontiers in Psychiatry, 2024)
Introduction: The prevailing view is that loneliness predominantly affects older adults.However, awareness of high rates of loneliness among younger populations is growing, prompting a call for interventions. The current study aimed to listen to the voices of young people regarding how they cope with loneliness, gaining a better understanding of how to then develop tailored interventions.Methods: Thirteen Arts-based focus groups were conducted with 74 participants (8-18 years old), in London, Manchester, and South Yorkshire. Reflexive thematic analysis was utilised.Results: We developed six themes as follows: (1) "Determinants of the coping approach for loneliness", (2) "Considerations to guide decision making", (3) "Coping strategies to alleviate loneliness", (4) "Social connection as a coping strategy for loneliness -considerations", ( 5) "Being active in your own coping success", and ( 6) "Worsening loneliness, coping strategies gone wrong".Conclusions: Participants described a partially sequential process in choosing coping strategies for loneliness, including effective and maladaptive choices. Effective strategies were highlighted, reflecting developmental stages with the need for self-motivation.Participants noted challenges in engaging in coping due to skill deficits. These findings are crucial for developing interventions specific to this population.